Eye Irritation Test of Fel Ursi, Bovis Calculus & Moschus Pharmacopuncture Solutions for Eye Drop - Hyeong-sik Seo (Korean Pharmacopuncture Institute, 2008)
Objective : The aim of this study is to investigate the safety of Fel Ursi, Bovis Calculus & Moschus pharmacopuncture solution manufactured with freezing dryness method to use eye drop. Methods : The eye irritation test of this material was performed according to the Regulation of Korea Food & Drug Administration(2005. 10. 21, KFDA 2005- 60). After Fel Ursi, Bovis Calculus & Moschus pharmacopuncture solution was applied eyewash in the left eye of the rabbits, the author observed eye irritation of the cornea, iris, conjunctiva at 1, 2, 3, 4 & 7day. Results : 1. After Fel Ursi, Bovis Calculus & Moschus pharmacopuncture solution was applied eyewash in the left eye of the rabbits, there wasn't physical problem at 9 rabbits. 2. After Fel Ursi, Bovis Calculus & Moschus pharmacopuncture solution was applied eyewash in the left eye of the rabbits, there wasn't eye irritation of the cornea, iris, conjunctiva at 1, 2, 3, 4 & 7day. Conclusions : In this study, it was observed that Fel Ursi, Bovis Calculus & Moschus pharmacopuncture solution didn't induced eye irritation in rabbits.